p62/SQSTM1-dependent autophagy of Lewy body-like α-synuclein inclusions. - Yoshihisa Watanabe; Harutsugu Tatebe; Katsutoshi Taguchi; Yasuhisa Endo; Takahiko Tokuda; Toshiki Mizuno; Masanori Nakagawa; Masaki Tanaka (PLoS ONE, 2012)
α-Synuclein is the main component of Lewy bodies, the intraneuronal inclusion bodies characteristic of Parkinson's disease. Although α-synuclein accumulation is caused by inhibition of proteasome and autophagy-lysosome, the degradation of α-synuclein inclusions is still unknown. Formation of Lewy body-like inclusions can be replicated in cultured cells by introducing α-synuclein fibrils generated in vitro. We used this cell culture model to investigate the autophagy of α-synuclein inclusions and impaired mitochondria. The intracellular α-synuclein inclusions immediately underwent phosphorylation and ubiquitination. Simultaneously they were encircled by an adaptor protein p62/SQSTM1 and directed to the autophagy-lysosome pathway in HEK293 cell line. Most phospho-α-synuclein-positive inclusions were degraded in 24 h, however, lysosomal dysfunction with bafilomycin A1 significantly affected their clearance. Moreover, inhibition of autophagy by Atg-5 siRNA treatment reduced the incorporation of α-synuclein inclusions into LC3-positive autophagosomes. Knockdown experiments demonstrated the requirement of p62 for α-synuclein autophagy. These results demonstrate that α-synuclein inclusions are preferred targets for p62-dependent autophagy. Next, we investigated the autophagic clearance of impaired mitochondria in α-synuclein inclusion-containing cells. Impaired mitochondria were almost completely eliminated after mitochondrial uncoupling even in the presence of α-synuclein inclusions, suggesting that mitochondrial clearance is not prevented by α-synuclein inclusions in HEK293 cells.